1993
DOI: 10.1017/s0021859600074220
|View full text |Cite
|
Sign up to set email alerts
|

Effects of competition with weeds on the growth, development and yield of sorghum

Abstract: S U M M A R YIn two field experiments in Suriname, competition between weeds and sorghum (Sorghum bicolor (L.) Moench) was studied in the rainy seasons of 1982 and 1983. The crop was kept either weed-free or without weed control for each of six different periods of time from planting. Observations made at the end of each period allowed an analysis to be made of the growth and development of a crop with and without weed control.Due to the crop canopy structure and fertilizer placement near the row, weed growth … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
14
0
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 19 publications
1
14
0
1
Order By: Relevance
“…Although weeds were removed with handweeding, the timing of removal may have led to weed competition in the plants (Everaarts, 1992;Van Heemst, 1985). Net income (fruit harvest minus weed management costs over the 3 years), not including other management costs which were assumed to be equivalent among weed management treatments, was $31,380/ha in the weed mat, 86% and 20% greater than in the non-weeded and handweeded systems, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Although weeds were removed with handweeding, the timing of removal may have led to weed competition in the plants (Everaarts, 1992;Van Heemst, 1985). Net income (fruit harvest minus weed management costs over the 3 years), not including other management costs which were assumed to be equivalent among weed management treatments, was $31,380/ha in the weed mat, 86% and 20% greater than in the non-weeded and handweeded systems, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…It is well established that the most critical period for cropweed competition in sorghum is 45 DAS. At initial stages, the sorghum grows slowly and is a weak competitor to most weeds; even minimal weed infestations in the early growth period reduce sorghum yields significantly (Everaarts 2003).…”
mentioning
confidence: 99%
“…Br.] (Limon‐Ortega et al, 1998); and annual weeds with grain sorghum (Everaarts, 1993) indicated that the number of kernels per panicle or ear was the yield component most sensitive to competition. In sorghum, the number of kernels per panicle is determined during the boot stage just before flowering (Vanderlip, 1993).…”
mentioning
confidence: 99%